MENINGKATKAN RESPONS SISWA KELAS VIII-DSMP NEGERI 15 PURWOREJOTERHADAP MATA PELAJARAN IPS PADA JAM TERAHIR MELALUI PRAMEK (PEMBELAJARAN REKREATIF, AKTIF, MENANTANG, EFEKTIF, DAN KONTEKSTUAL) - Sholeh, Muh.; Kadari, Kusnan (Universitas Negeri Semarang, 2011)
The purpose of this study was to improve the response of students to the social studies lesson on the last clock marked with students listening to teacher explanations, dare to answer questions, actively working on the task, courage to ask, and dare to express an opinion. Steps to be taken is the action planning and execution. Planning carried out by identifying the various problems that arise in every process pembelajaranr, while the action taken was to conduct recreational learning, active, challenging, effective, and contextual (PRAMEK). Implementation PRAMEK to increase students responses did not walk easily. The cause is still difficult to translate PRAMEK teachers in learning in the classroom, not fully ihlas make changes learning, still think the class is indeed different from other classes, and still trying to find a formula that is more fitting in implementing the learning. Learning from previous experience of the master teacher PRAMEK. In implementing the teacher learning the more comfortable carrying out learning so that students responses have increased in accordance with the purpose of research.